Demographic and Clinical Correlates of High-lethality Suicide Attempts: A Retrospective Study in Psychiatric Inpatients. Issue 6 (November 2021) - Berardelli, Isabella; Innamorati, Marco; Sarubbi, Salvatore; Rogante, Elena; Erbuto, Denise; Lester, David; Pompili, Maurizio
Abstract : Assessment of the lethality of suicide attempts is a neglected topic in the literature in this area. Based on the hypothesis that suicide attempters who choose a highly lethal method differ from those who use less lethal methods, we analyzed the characteristics of suicide attempters who used different suicide methods to determine demographic and clinical risk factors for the lethality of suicide methods. For this purpose, we used the Risk-Rescue Rating Scale to assess the lethality of the suicide method in a consecutive sample of 107 psychiatric inpatients with a recent suicide attempt (in 6 mo before hospitalization). The results demonstrated that patients who used a highly lethal method were younger and more frequently single. A novel finding of this study was that earlier age of onset of psychiatric symptoms and a higher number of previous hospitalizations were associated with the use of more lethal methods. In conclusion, patients who used more lethal methods differed from those who used less lethal methods. Identification of these differences may be necessary to implement specific suicide prevention strategies in patients with psychiatric conditions.